Development and Analysis of Geographic Information System for Electricity Network (Case Study: Surabaya Industrial Estate Rungkut in Surabaya). - Awalin, Lilik Jamilatul; Sukojo, Bangun Muljo (Makara Journal of Technology, 2003)
Development and Analysis of Geographic Information System for Electricity Network (Case Study: Surabaya Industrial Estate Rungkut in Surabaya). Geographic Information System (GIS) is a system of data which has spatial base. This may be cause has ability to process and analysis data quickly. The ability of GIS will be able to process the alternative in decision making. The need of electric power grows until recent time along with the existence of industrial sector expansion and land use expansion claim better service, large and balance stock of electric power. GIS is a solution for planning and managing data base system, for quickly service and professional service to consumer in Surabaya Industrial Estate Rungkut (SIER) Area. By using Arc View to process the data which has spatial base, and supported by energy and voltage data in Surabaya Industrial Estate Rungkut area, the resistance, current, voltage regulation, energy losses supplied by Surabaya Industrial Estate Rungkut can be calculated. The existence of GIS technology can assist the work process in operator level and the balance of electrical power efficiency.